Prevalensi dan identifikasi ektoparasit pada ikan Patin (Pangasius djambal) pada kolam tadah hujan di Kecamatan Seruyan Hilir Kabupaten Seruyan. - Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
The purpose of this study was to determine the various types of parasites and to determine the prevalence of infection of ectoparasites on the catfish (Pangasius djambal) culture at District Seruyan Hilir, Seruyan Regency. The highest prevalence of ectoparasites on catfish in rain-fed pond was at the pond 2, that were Dactylogyrus sp. (0% fin, gills 50%, mucus 0%), Ichtyophthirus multifilis (fin 10%, 10% gills, mucus 30%), and Trichodina sp. (Fin 0%, 0% gills, mucus 20%). While the lowest was pond 1, that were Dactylogyrus sp (Fin 0%, 30% gills, mucus 20%), Ichtyophthirus multifilis (10% fins, gills 0%, mucus 20%), and Trichodina sp. (Fin 0%, 0% gills, mucus 20%). The highest intensity of ectoparasite attacks on catfish was at the pond 2, that were Dactylogyrus sp. (fin 0 ind / tail, gills 5.2 ind / tail, mucus 0 ind / tail), Ichtyophthirus multifilis (fin 3 ind / tail, gills 2 ind / tail, mucus 5.6 ind / tail), and Trichodina sp. (fin 0 ind / tail, gills 0 ind / tail, mucus 2.5 ind / tail), while the lowest was pond 1, that were Dactylogyrus sp (fin 0 ind / tail, gills 4.6 ind / tail, mucus 0 ind / tail), Ichtyophthirus multifilis (fin 3 ind / tail, gills 0 ind / tail, mucus 4.5 ind / tail), and Trichodina sp. (fin 0 ind / tail, gills 0 ind / tail, mucus 2 ind / tail). Key words : Parasites, Prevalence, Pangasius djambal.